RELIGION, CULTURE AND EDUCATION IN THE CONTEXT OF TRIBAL ASPIRATIONS IN INDIA - Minz, Nirmal (Journal of Dharma, 1999)
Tribal problems, and how to solve them, have been widely discussed by Government and private agencies including the Christian Church in India. In this discussion education of Tribals occupies a prominent place. Huge amounts of material and human resources have already been spent at local, state and national levels on Tribal Welfare, which includes their education. Many articles and books have been published on problems relating to Tribal education in Indial. This paper takes note of them but it has attempted to adopt a different approach to tribal education in discussing the problems. The attitude that tribals are objects of welfare/development as reflected in most of the materials is resisted and rejected in the process" A small beginning is made here to explore the vision and understanding of education of Tribals as authors of their own destiny.